2018
DOI: 10.4103/ijmm.ijmm_18_12
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasmosis in Non-endemic North-Western Part of India

Abstract: This study highlights that Gujarat and Rajasthan are an endemic region for histoplasmosis, and a systematic study is required to understand epidemiology of the disease. Histoplasmosis should be a differential diagnosis in a patient presenting with adrenal enlargement, lymphadenopathy, oral ulcers and fever of unknown origin in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Very few cases were reported from the nonendemic region of India like Rajasthan. Patel et al reported 7 cases of histoplasmosis from Rajasthan [6]. We report this case from the hot and dry climate area of the Western India.…”
Section: Discussionmentioning
confidence: 72%
“…Very few cases were reported from the nonendemic region of India like Rajasthan. Patel et al reported 7 cases of histoplasmosis from Rajasthan [6]. We report this case from the hot and dry climate area of the Western India.…”
Section: Discussionmentioning
confidence: 72%
“…Histoplasma was first isolated from soil in Malaysia in 1963, and Randhawa reviewed 30 possible autochthonous cases from India, Malaysia, Indonesia, Singapore, Thailand, Vietnam, and Japan in 1970 [ 61 , 62 ]. There have been 144 cases of histoplasmosis recorded from 1954 through 2017 in India with the majority of reports from West Bengal, Assam, Bihar, Delhi, Haryana, Punjab, and Uttar Pradesh; as in many other settings, histoplasmosis is felt to be underdiagnosed in this country [ 63 65 ]. Histoplasmin sensitivities in Kolkata and Delhi range from 4.7–12.3% [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…Systemic histoplasmosis is ubiquitous, and the causative fungus is found in the soil fertilized by birds, chicken, and bats. [ 1 2 3 4 ] Histoplasmosis is common in immunosuppressed individuals and may present with mild influenza, which often leads to granulomatous disease and can even progress to life-threatening disease. [ 1 2 3 4 ] In developing countries such as India, it can mimic tuberculosis.…”
mentioning
confidence: 99%
“…[ 1 2 3 4 ] Histoplasmosis is common in immunosuppressed individuals and may present with mild influenza, which often leads to granulomatous disease and can even progress to life-threatening disease. [ 1 2 3 4 ] In developing countries such as India, it can mimic tuberculosis. [ 3 4 ] Ocular manifestations of systemic histoplasmosis include retinitis, choroiditis, optic neuritis, uveitis, and endophthalmitis.…”
mentioning
confidence: 99%
See 1 more Smart Citation